DENUDATION EFFECT OF TERMITARIA AND CHARACTERIZATION OF ASSOCIATED TERMITE SPECIES IN LAFIA NASARAWA STATE, NIGERIA - Mohammed, Musa; Abiodun, Ajayi Folorunso; Jibia, Abdulhadi Bawa (European Scientific Journal, ESJ, 2014)
Termite infestation is an important factor in the livelihood of the dwellers in the savanna region of Nigeria. This study evaluates the denudation effect of termitarium and characterization of associated termites’ species in Lafia Local Government of Nasarawa State of Nigeria. Structured questionnaire was administered to 21 farmers at random to access information on the effect of termite infestation on crops, the loss incurred due to termite infestation, the type of crop the farmers grow, the yield of the crop after harvest, farm size, and the total area denuded by termites in the study area. Also representative sample of termites’ species was taken and identified. The respond of the farmers was subjected to simple statistics for analysis, the termite species found include: Odontotermes, Callotermes, Eutermes and Termes species. The mean width and height of termitarium, the mean of farm size were obtained after the analysis. The total area denuded by each termite species was determined after the analysis and it was found that Odontotermes (47.9%) was found to cause larger termitaria than Callotermes (42.9%), Termes, and Eutermes that recorded 4.8%, respectively. Thus, Odontotermes caused more denudation of farm land than other species found in the study area.